Self-medication and knowledge of pregnant women about the use of medication during pregnancy in the cities of Rijeka and Zadar, Croatia - Jovanović, Željko; Vulić, Petra (Frontiers in Pharmacology, 2025)
ObjectivesPregnancy is a sensitive period during which the use of medicines, whether by prescription or self-medication, is a major challenge as it can have a significant impact on the health of the mother and the development of the foetus. It is important that pregnant women are well-informed about potential risks and benefits and seek advice from healthcare professionals before taking any medication, including over-the-counter medications, to ensure the safety and health of themselves and their unborn child. The aim of this study was to analyse the self-medication practices of pregnant women and their knowledge and attitudes toward medicines in the context of pregnancy. This includes analysing the way pregnant women make decisions about self-medication and their awareness of potential risks and benefits.MethodsA cross-sectional study was conducted on a sample of pregnant women from two cities of similar size and status, Zadar and Rijeka, in the period from 1 May 2023 to 1 June 2023 at the Clinical Hospital Centre Rijeka and the General Hospital Zadar.ResultsOf the 128 women interviewed, 56% were taking prescription medication, most frequently in Rijeka, while 69.5% practised self-medication. The most commonly used medications were dietary supplements—75 (44.88%); over-the-counter pain relievers and fever, cough, allergy, cold, and nausea remedies—42 (33.07%); and herbal medicines—8 (6.29%).ConclusionPregnant women need to be better informed about self-medication and the safe use of medication. A total of 94.5% of respondents consider it important to improve educational programmes and access to information about the effects of medication on the health of the foetus and pregnancy outcomes.